Zinc Oxide Nanoparticles Influence Microflora in Ileal Digesta and Correlate Well with Blood Metabolites - Feng, Yanni; Min, Lingjiang; Zhang, Weidong; Liu, Jing; Hou, Zhumei; Chu, Meiqiang; Li, Lan; Shen, Wei; Zhao, Yong; Zhang, Hongfu (Frontiers in Microbiology, 2017)
Zinc oxide nanoparticles (ZnO NPs) are used widely in consumer and industrial products, however, their influence on gut microbiota and metabolism and their mutual interactions are not fully understood. In this study, the effects of ZnO NPs on ileal bacterial communities, plasma metabolites, and correlations between them were investigated. Hens were fed with different concentrations of ZnO NPs (based on Zn; 0 mg/kg (control), 25 mg/kg, 50 mg/kg, and 100 mg/kg) for nine weeks. Subsequently, ileal digesta and blood plasma were collected for analysis of microflora and metabolites, respectively. The V3-V4 region of the 16S rRNA gene of ileal digesta microbiota was sequenced using the Illumina HiSeq2500 platform. The predominant bacterial community in the ileum belongs to the phylum Firmicutes. The richness of the bacterial community was negatively correlated with increasing amounts of ZnO NPs (r = -0.636, P < 0.01); when ZnO NP levels were at 100 mg/kg, microbiota diversity was significantly decreased (P < 0.05). The community structure determined by LEfSe analysis indicated that Bacilli, Fusobacteria, and Proteobacteria were changed, and Lactobacillus was reduced by ZnO NPs. Moreover, metabolism as analyzed by nuclear magnetic resonance (NMR) indicated that glucose, some amino acids, and other metabolites were changed by ZnO NPs. Choline, lactate, and methionine were positively correlated with bacterial richness. In summary, ZnO NPs could influence the levels of microflora in ileal digesta, particularly Lactobacillus. Furthermore, the richness of the microbiota was related to changes in choline, lactate, and methionine metabolism.